(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
Most of us are familiar with pneumonia today. The reason is that the incidence of this disease has recently been observed in our country as well as in the whole world. Unfortunately, this disease does not spare children. This can be attributed to the worldwide pandemic situation, the emergence of new strains of the "Covid-19" infection, and the fact that the same strains are often found in children. In addition, several other factors are causing the increase in lung disease in children. In particular, when viral infections spread through air-drops increase, the child does not follow the rules of personal hygiene, does not use protective equipment correctly, and several other reasons lead to this disease.